2017
DOI: 10.3389/fendo.2017.00261
|View full text |Cite
|
Sign up to set email alerts
|

Macropinocytosis: A Metabolic Adaptation to Nutrient Stress in Cancer

Abstract: Oncogenic mutations, such as Ras mutations, drive not only enhanced proliferation but also the metabolic adaptations that confer to cancer cells the ability to sustain cell growth in a harsh tumor microenvironment. These adaptations might represent metabolic vulnerabilities that can be exploited to develop novel and more efficient cancer therapies. Macropinocytosis is an evolutionarily conserved endocytic pathway that permits the internalization of extracellular fluid via large endocytic vesicles known as macr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
179
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 186 publications
(184 citation statements)
references
References 71 publications
5
179
0
Order By: Relevance
“…Multiple proteins and signalling factors are involved in macropinocytosis, including the Rho superfamily of GTPases (Rac, Cdc42), lipid components (phosphoinositides, cholesterol, phosphatidylinositol phosphates), phospholipid kinases, receptor tyrosine kinases and phosphatases, SNX‐5 and DKK‐3 . There is also large body of evidence that now shows macropinocytosis can be specifically activated by extracellular stimuli, such as growth factors and natural or synthetic chemicals, and the activated macropinocytosis can have effects on cell survival/proliferation or cell death/growth inhibition on distinct cell types including cancer cells …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple proteins and signalling factors are involved in macropinocytosis, including the Rho superfamily of GTPases (Rac, Cdc42), lipid components (phosphoinositides, cholesterol, phosphatidylinositol phosphates), phospholipid kinases, receptor tyrosine kinases and phosphatases, SNX‐5 and DKK‐3 . There is also large body of evidence that now shows macropinocytosis can be specifically activated by extracellular stimuli, such as growth factors and natural or synthetic chemicals, and the activated macropinocytosis can have effects on cell survival/proliferation or cell death/growth inhibition on distinct cell types including cancer cells …”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10][11][12][13][14][15][16] There is also large body of evidence that now shows macropinocytosis can be specifically activated by extracellular stimuli, such as growth factors and natural or synthetic chemicals, and the activated macropinocytosis can have effects on cell survival/proliferation or cell death/growth inhibition on distinct cell types including cancer cells. 17,18 Meridianin C is one of the marine derived indole alkaloids (meridianin A-G) isolated from the South Atlantic tunicate Aplidium meridianum. 19,20 Previously, meridianin C, D or G analogues/derivatives have been shown to inhibit the proliferation of human breast (MCF-7) and cervix (HeLa) cancer and leukaemia (MV4-11) cells.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies demonstrated that macropinocytosis, through uptake of extracellular proteins (e.g. albumin) and their further degradation in lysosomes, enables cancer cells to survive in a nutrient-poor tumor microenvironment (Commisso et al, 2013;Lee et al, 2019;Palm, 2019;Recouvreux & Commisso, 2017). However, the majority of these studies concentrated on macropinocytosis triggered by mutated RAS and/or were conducted in pancreatic cancer cells, whereas data on RTK-mediated macropinocytosis as an alternative nutrient uptake route in other cancer types were lacking.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that pancreatic cancer cells expressing oncogenic RAS upregulate macropinocytosis to acquire extracellular albumin which, upon lysosomal degradation, provides amino acids for the metabolism and cell growth. In this way, macropinocytosis allows cancer cells to survive in a nutrient-poor tumor microenvironment (Commisso et al, 2013;Palm, 2019;Recouvreux & Commisso, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally the metabolic stress conditions were found to increase the membrane ruffling and formation of actin rich macropinocytosis. Abundance of macropinocytes or cytoneme like structure in stressed spheroids might control the entosis or nutrient-scavenging mechanisms to support the tumorogenesis within the nutrient-deprived environments 48 .…”
Section: Discussionmentioning
confidence: 99%